To stream or not to stream? : A case of social media management within a professional sport organization - Wymer, Sarah; Naraine, Michael L., 1987-; Thompson, Ashleigh-Jane; Martin, Andy J. (London : Human Kinetics, Inc., 2020)
This is a fictional case based on the actual management of a social media strategy that occurred in a professional sport organization in Queensland, Australia. The intention of the case is to explore a range of social media management themes such as live streaming, audience reach, fan engagement, and decision making as they apply to a sport organization. The case primarily focuses on social media live streaming (specifically Facebook Live) and aims to provide an understanding of live video posts in comparison with other post types (i.e., photo, video, text, and links). The case develops within the theoretical frameworks of relationship marketing, fan engagement, and social media, and is suitable for students learning about sport marketing, sport sponsorship, promotion and public relations, and other communication courses in sport management. Specifically, students are tasked with developing a range of potential strategies to support the lead character, Michael Battersby, in implementing live streaming within a social media strategy.
Orginally Published InWymer, S., Naraine, M. L., Thompson, A. J., & Martin, A. J. (2020). To Stream or Not to Stream? A Case of Social Media Management Within a Professional Sport Organization. Case Studies in Sport Management, 9(1), 26-34.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports administration -- Queensland -- Case studies; Communication in sports -- Queensland -- Case studies; Live streaming -- Case studies